Method for changing surface performance of collagen casing

By adding a specific amount of cellulose to hydrochloric acid solution during the wet preparation of collagen casings, a stable colloid is formed, which solves the problems of rough surface of dry casings and slippage and difficulty in tying wet casings, thereby improving the surface properties of casings and making packaging more convenient.

CN119278988APending Publication Date: 2025-01-10DEFULE (NANTONG) TECH CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411737142.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing dry-process collagen casings have a rough but thick surface and a tough texture, while wet-process casings have a slippery surface that is difficult to tie and become astringent after steaming or cooking, which affects sausage packaging.

Method used

By adding a specific amount of cellulose to the hydrochloric acid solution during the wet preparation process and mixing it with the glue, a stable collagen colloid is formed, which increases the surface roughness of the casing and improves the chemical bonding, thereby adjusting the friction after cooking.

Benefits of technology

While ensuring the taste of wet-process sausage casings, the surface roughness of the casings is increased, improving the tying performance, reducing friction after cooking, facilitating packaging, and simplifying the preparation process.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a method for changing the surface performance of a collagen casing. The method comprises the following steps: treating cow split leather treated by a peeling machine by using an ammonium sulfate solution, and then treating the cow split leather by using a buffer solution; the preparation method comprises the following steps: uniformly mixing cleaned cow split leather with ice water, dicing and grinding to obtain collagen leather pulp; mixing the mucilage and a hydrochloric acid solution, adding cellulose into the hydrochloric acid solution to obtain a crude collagen colloid, and standing until the colloid is fully swelled; and homogenizing by using a homogenizer, extruding by using an extruder, and drying to obtain the tubular collagen casing. The preparation method has the advantages that the collagen casing is prepared by a wet method, a specific amount of cellulose is added during preparation to enter a network structure originally independently formed by collagen, the network space is filled, the surface roughness of the casing is increased, and meanwhile, the cellulose is combined with collagen molecules through chemical bonds to increase the stability of the network structure, so that the collagen casing is prepared. The surface performance of the casing is changed, the surface roughness is increased, the friction force between the sausage and a package is small, and the sausage is easier to package.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of collagen casings, and in particular to a method for changing the surface properties of collagen casings. Background Art

[0002] There are two methods for preparing collagen casings: dry method and wet method. The conventional casing preparation method is mainly dry method. The collagen fibers of the existing dry method are not completely broken, the collagen fibers are coarse, and the surface of the casing is rough. However, the casing prepared by the dry method is thick, and the sausage has a stale taste. The cellulose added in the dry method is mainly microcrystalline cellulose. The conventional casing preparation method has high requirements for the size of cellulose, and mainly selects microcrystalline cellulose. Microcrystalline cellulose is a white, odorless and tasteless crystalline powder composed of natural cellulose that has been hydrolyzed with dilute acid to the limit degree of polymerization and is free-flowing, extremely fine short rods or powdery porous particles. The particle size is generally 20-80μm. Since microcrystalline cellulose is dispersed into the collagen colloid, there is a maximum limit to the amount of cellulose added. If there is more, it will settle and cannot enter the collagen colloid. Before adding, the microcrystalline cellulose needs to be dispersed in the sand-filtered water. It needs to be prepared and used immediately, and then added to the collagen colloid. After being mixed and kneaded with the colloid by a machine, it is squeezed out into the casing through an extruder.

[0003] The collagen fibers of the casings prepared by the conventional wet method are small and highly uniform. The surface of the casings obtained is delicate and smooth, and the sausages prepared are soft and tender. However, the surface of the sausages prepared by the wet method is slippery before cooking, and the sausages are easy to slip in the wire tying machine and difficult to tie. At the same time, the surface of the sausages is astringent after cooking, and the friction between the sausages and the packaging increases, making it difficult to package. It is necessary to provide a method for changing the surface properties of collagen casings, which can change the surface properties of collagen casings, increase the surface roughness of casings, facilitate the tying of sausages in the wire tying machine, and adjust the friction of the sausage surface after cooking to facilitate packaging while ensuring the taste of sausages made by wet casings. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for changing the surface properties of collagen casings, which can solve the problems in the prior art that the surface of casings prepared by dry method is rough but the casings are thick, the sausages have a stale taste, the surface of casings prepared by wet method is slippery, making the sausages slippery in the wire tying machine and difficult to tie, and the surface of sausages is astringent after steaming, which increases the friction between the sausages and the packaging and makes them difficult to package.

[0005] In order to solve the above technical problems, the technical solution of the present invention is: comprising the following steps: S1, take the cow split leather treated by the peeling machine, treat it with ammonium sulfate solution, wash it with water, and then treat it with buffer solution to control the pH value of the leather to 4.6, and then wash it with water; S2, uniformly mixing the cleaned cow split hide with ice water in a ratio of 1:2, dicing and grinding, to obtain collagen hide slurry; S3, mixing the slurry and 1.26% w / w hydrochloric acid solution, wherein the hydrochloric acid solution is diluted with 31.5% hydrochloric acid as the stock solution, cellulose is added to the hydrochloric acid solution, and a crude collagen colloid is obtained, and the colloid is allowed to stand until it is fully swollen; S4. Use a homogenizer to homogenize to obtain a uniform and stable collagen colloid, extrude it through an extruder, and obtain a tubular collagen casing after drying.

[0006] Furthermore, in step S3, the amount of cellulose added to the hydrochloric acid solution is 0.9-4.5% w / w.

[0007] Furthermore, in step S1, the concentration of the ammonium sulfate solution is 0.4% w / w.

[0008] Furthermore, in step S1, the buffer contains 0.5% w / w citric acid and 0.7% w / w sodium citrate.

[0009] Furthermore, in step S3, the mixed glue and the hydrochloric acid solution are mixed in a mass ratio of 1:1.

[0010] The invention has the advantages that: collagen casing is prepared by wet method, and a specific amount of cellulose is added during preparation to enter the network structure originally formed by collagen alone, fill the network space, increase the surface roughness of the casing, and at the same time combine with collagen molecules through chemical bonds to increase the stability of the network structure, and the cellulose is added in a 1.26% (w / w) hydrochloric acid solution and mixed with the glue, so that the surface performance of the casing is changed, and the surface roughness of the casing is increased while ensuring the taste of the sausage made by the wet casing, so that the sausage is easy to tie in the wire tying machine, and the friction force on the surface of the sausage after steaming is adjusted, so that the friction force between the sausage and the package is small, and it is easier to package; The cellulose added to the hydrochloric acid solution is not limited in size, and the amount of cellulose added can be adjusted, so there will be no problem of sedimentation if there is too much cellulose. There is no need to disperse the cellulose in the sand filtration water for immediate use, so the preparation is more convenient. DETAILED DESCRIPTION

[0011] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with specific implementation methods. The following examples can enable technicians in this field to understand the present invention more comprehensively, but the present invention is not limited to the scope of the embodiments.

[0012] This specific implementation adopts the following technical solution: comprising the following steps: S1, take the cow split leather treated by the peeling machine, treat it with 0.4% w / w ammonium sulfate solution, wash it with water, and then treat it with a buffer solution containing 0.5% w / w citric acid and 0.7% w / w sodium citrate, control the pH value of the leather to 4.6, and then wash it with water; S2, uniformly mixing the cleaned cow split hide with ice water in a ratio of 1:2, dicing and grinding, to obtain collagen hide slurry; S3, mixing the glue and 1.26% w / w hydrochloric acid solution in a mass ratio of 1:1, wherein the hydrochloric acid solution is diluted with 31.5% hydrochloric acid as the stock solution, and 0.9-4.5% w / w cellulose is added to the hydrochloric acid solution to obtain a crude collagen colloid, and standing the colloid until it is fully swollen; S4. Use a homogenizer to homogenize to obtain a uniform and stable collagen colloid, extrude it through an extruder, and obtain a tubular collagen casing after drying.

[0013] Example 1: Take the cow split leather treated by a peeling machine, treat it with 0.4% (w / w) ammonium sulfate solution, wash it with water, and then treat it with a buffer solution containing 0.5% (w / w) citric acid and 0.7% (w / w) sodium citrate, control the pH of the leather material to be around 4.6, then wash it with water, and evenly mix the cleaned cow split leather with ice water in a ratio of 1:2, cut and grind it, and obtain collagen leather pulp; mix the glue pulp and 1.26% (w / w) hydrochloric acid solution in a ratio of 1:1, and dilute the hydrochloric acid solution with 31.5% concentration hydrochloric acid as the stock solution, which contains 0.9% cellulose, to obtain a crude collagen colloid, and let it stand until the colloid is fully swollen; use a homogenizer to homogenize to obtain a uniform and stable collagen colloid; extrude it through an extruder, and obtain a tubular collagen casing after drying.

[0014] Example 2: Take the cow split leather treated by a peeling machine, treat it with 0.4% (w / w) ammonium sulfate solution, wash it with water, and then treat it with a buffer solution containing 0.5% (w / w) citric acid and 0.7% (w / w) sodium citrate, control the pH of the leather to be around 4.6, then wash it with water, mix the cleaned cow split leather with ice water in a ratio of 1:2 and grind it into particles to obtain collagen leather pulp, mix the glue pulp and 1.26% (w / w) hydrochloric acid solution in a ratio of 1:1, dilute the hydrochloric acid solution with 31.5% concentration hydrochloric acid as the stock solution, containing 1.8% cellulose, to obtain a crude collagen colloid, and let it stand until the colloid is fully swollen; use a homogenizer to homogenize to obtain a uniform and stable collagen colloid; extrude it through an extruder and dry it to obtain a tubular collagen casing.

[0015] Example 3: Take the cow split leather treated by a peeling machine, treat it with 0.4% (w / w) ammonium sulfate solution, wash it with water, and then treat it with a buffer solution containing 0.5% (w / w) citric acid and 0.7% (w / w) sodium citrate to control the pH of the leather to be around 4.6, then wash it with water, and evenly mix the cleaned cow split leather with ice water in a ratio of 1:2, and grind it into particles to obtain collagen leather pulp, and mix the glue pulp and 1.26% (w / w) hydrochloric acid solution in a ratio of 1:1, and dilute the hydrochloric acid solution with 31.5% concentration hydrochloric acid as the stock solution, which contains 2.7% cellulose, to obtain a crude collagen colloid, and let it stand until the colloid is fully swollen; use a homogenizer to homogenize to obtain a uniform and stable collagen colloid; extrude it through an extruder, and dry it to obtain a tubular collagen casing.

[0016] Example 4: Take the cow split leather treated by a peeling machine, treat it with 0.4% (w / w) ammonium sulfate solution, wash it with water, and then treat it with a buffer solution containing 0.5% (w / w) citric acid and 0.7% (w / w) sodium citrate to control the pH of the leather to be around 4.6, then wash it with water, and evenly mix the cleaned cow split leather with ice water in a ratio of 1:2, and grind it into particles to obtain collagen leather pulp, and mix the glue pulp and 1.26% (w / w) hydrochloric acid solution in a ratio of 1:1, and dilute the hydrochloric acid solution with 31.5% concentration hydrochloric acid as the stock solution, which contains 3.6% cellulose, to obtain a crude collagen colloid; let it stand until the colloid is fully swollen; use a homogenizer to homogenize to obtain a uniform and stable collagen colloid; extrude it through an extruder, and obtain a tubular collagen casing after drying.

[0017] Example 5: Take the cow split leather treated by a peeling machine, treat it with 0.4% (w / w) ammonium sulfate solution, wash it with water, and then treat it with a buffer solution containing 0.5% (w / w) citric acid and 0.7% (w / w) sodium citrate to control the pH of the leather to be around 4.6, then wash it with water, and evenly mix the cleaned cow split leather with ice water in a ratio of 1:2, and grind it into particles to obtain collagen leather pulp, and mix the glue pulp and 1.26% (w / w) hydrochloric acid solution in a ratio of 1:1, and dilute the hydrochloric acid solution with 31.5% concentration hydrochloric acid as the stock solution, which contains 4.5% cellulose, to obtain a crude collagen colloid, and let it stand until the colloid is fully swollen; use a homogenizer to homogenize to obtain a uniform and stable collagen colloid; extrude it through an extruder, and dry it to obtain a tubular collagen casing.

[0018] Comparative Example 1: Take the cow split leather treated by a peeling machine, treat it with 0.4% (w / w) ammonium sulfate solution, wash it with water, and then treat it with a buffer solution containing 0.5% (w / w) citric acid and 0.7% (w / w) sodium citrate to control the pH of the leather to be around 4.6, then wash it with water, mix the cleaned cow split leather with ice water in a ratio of 1:2 and grind it into particles to obtain collagen leather pulp, mix the glue pulp and 1.26% (w / w) hydrochloric acid solution in a ratio of 1:1, dilute the hydrochloric acid solution with 31.5% concentration hydrochloric acid as the stock solution to obtain crude collagen colloid, and let it stand until the colloid is fully swollen; use a homogenizer to homogenize to obtain a uniform and stable collagen colloid; extrude it through an extruder and dry it to obtain a tubular collagen casing.

[0019] The casings prepared in Examples 1-5 and Comparative Example 1 were subjected to roughness test, friction test on the sausage surface after cooking, knot loosening and shear speed test, and casing length test. The test results are shown in Tables 1 to 4.

[0020] Table 1: Casing roughness test results: sample Ra(µm) Rq(µm) Rz(µm) Comparative Example 1 4.02 4.88 17.54 Example 1 4.62 5.59 20.76 Example 2 5.37 6.51 24.79 Example 3 5.57 7.00 26.56 Example 4 6.43 7.86 30.08 Example 5 6.55 7.92 32.35 Table 2: Friction test results of sausage surface after cooking: sample Static friction g Dynamic friction g Comparative Example 1 49.34 38.22 Example 1 20.86 16.03 Example 2 17.47 13.38 Example 3 16.52 13.02 Example 4 15.23 12.41 Example 5 14.95 12.35 Table 3: Debonding and shear rate test results: sample Number of sausage knots (pcs) Dispersion rate (%) Shear speed (number of shear kinks / min) Comparative Example 1 256 9% 455 Example 1 271 8.10% 520 Example 2 259 4.20% 520 Example 3 258 3.20% 585 Example 4 255 2.60% 650 Example 5 256 2.50% 650 Table 4: Casing strength test results: sample Cold drawing(N) Thermal stretching (N) Comparative Example 1 13.37 5.06 Example 1 12.43 4.71 Example 2 12.12 4.16 Example 3 11.61 3.20 Example 4 9.12 2.76 Example 5 6.13 1.26 From the above test data, it can be seen that the surface properties of the prepared collagen casings are changed by adding a specific amount of cellulose to the hydrochloric acid solution during the preparation and mixing with the slurry. The surface roughness of the casings prepared in Examples 1-5 is significantly better than that in Comparative Example 1, making it easier to tie the sausages in the wire-tying machine, and as the amount of cellulose added increases, the roughness increases; the friction force on the surface of the sausages prepared in Examples 1-5 after cooking is significantly less than that in Comparative Example 1, making the sausages non-sticky, the friction force between the sausages and the packaging is small, and it is easier to package, and as the amount of cellulose added increases, the friction force decreases; the casings prepared in Examples 1-5 The strength of the casing is not as good as that of comparative example 1, indicating that when the amount of cellulose added is small, there is no obvious effect on the improvement of the surface performance of the casing, and when the amount of cellulose added increases, it will significantly affect the tensile strength of the casing. In practical applications, the appropriate amount of cellulose added can be selected according to the required strength of the casing; the surface performance of the casings prepared in Examples 1-5 is improved, which is significantly better than that of comparative example 1. The friction between the surface of the sausages made from the casings prepared in Examples 1-5 and the packaging material is reduced, the unbundling rate of the sausages during filling is reduced, and the shearing speed of the shearing machine is increased. As the amount of cellulose added increases, the unbundling rate gradually decreases, and the shearing speed of the shearing machine gradually increases.

[0021] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for changing the surface properties of collagen casings, characterized in that: The following steps are involved: S1, take the cow split leather treated by the peeling machine, treat it with ammonium sulfate solution, wash it with water, and then treat it with buffer solution to control the pH value of the leather to 4.6, and then wash it with water; S2, uniformly mixing the cleaned cow split hide with ice water in a ratio of 1:2, dicing and grinding, to obtain collagen hide slurry; S3, mixing the slurry and 1.26% w / w hydrochloric acid solution, wherein the hydrochloric acid solution is diluted with 31.5% hydrochloric acid as the stock solution, cellulose is added to the hydrochloric acid solution, and a crude collagen colloid is obtained, and the colloid is allowed to stand until it is fully swollen; S4. Use a homogenizer to homogenize to obtain a uniform and stable collagen colloid, extrude it through an extruder, and obtain a tubular collagen casing after drying.

2. A method for changing the surface properties of collagen casing according to claim 1, characterized in that: In step S3, the amount of cellulose added to the hydrochloric acid solution is 0.9-4.5% w / w.

3. The method for changing the surface properties of collagen casing according to claim 1, characterized in that: In step S1, the concentration of the ammonium sulfate solution is 0.4% w / w.

4. The method for changing the surface properties of collagen casing according to claim 1, characterized in that: In step S1, the buffer contains 0.5% w / w citric acid and 0.7% w / w sodium citrate.

5. The method for changing the surface properties of collagen casing according to claim 1, characterized in that: In the step S3, the mixed glue and the hydrochloric acid solution are mixed in a mass ratio of 1:1.

Citation Information

Cited By

  • Preparation method of collagen casing

    CN121176492A

  • Production method of collagen casing with high surface roughness

    CN121312667A

  • A method for making collagen sausage casing

    CN122767377A